PEMANFAATAN APLIKASI EXPERT CHOICE SEBAGAI ALAT BANTU DALAM PENGAMBILAN KEPUTUSAN (STUDI KASUS: PT. BIT TEKNOLOGI NUSANTARA) - Handayani, Rani Irma (LPPM Universitas Nusa Mandiri, 2015)
PT. BIT TECHNOLOGY NUSANTARA need a laptop for the operations of the company because there are many laptop brands, PT. BIT difficulty in choosing a laptop brand that will be used for the operations of the company in accordance with the wishes and budget. In connection with this, then designed a decision support system for selecting a laptop using Hierarchy Analytical Process ( AHP). In making this decision the authors conducted several stages: Intelligent, Modelling, Choice. The tools that I use in this study is the Expert Choice (EC ) EC 2000 is a software application that can be used as one tool to assist decision makers in determining the decision.